Interaction of Agriculture and Farm Mechanization-paving the Path for Transformed Indian Agriculture: A Case Study of Mechanized Harvesting and Threshing of Chickpea in India - , Shilpa .P. Chowti; , Saraswathi J. M. (Archives of Current Research International, 2024)
The present study attempted to evaluate the financial feasibility of custom hiring of machines for harvesting and threshing of chickpea in two major chickpea growing states of India namely Maharashtra and Madhya Pradesh. The study was based on data collected from field survey. Two major states namely, Maharashtra and Madhya Pradesh were selected based on the area under chickpea. A multistage sampling procedure was adopted for the selection of study area, sample farmers and machine owners. The study was based on 90 samples of which 60 were chickpea growing farmers and 30 were machine owners. Farm budgeting, financial feasibility and Garrett ranking techniques were used to analyze the data. About 70 per cent of the sample farmers harvested chickpea engaging human labour and threshed it with machine and remaining 30 per cent of the sample farmers have used machine both for harvesting and threshing. The net profit of mechanical harvesting and threshing over manual harvesting and machine threshing was Rs. 2613 and Rs.3044 in Maharashtra and Madhya Pradesh respectively. Cultivation of spreading type of chickpea variety was the major constraint in adoption of mechanization. Investment on combined harvester was financially feasible and economically viable with NPV, Benefit Cost Ratio and IRR of Rs. 3307101.18, 2.91 and 25.52 per cent, respectively and payback period was 5.12 years. Investment on thresher was found to be profitable, financially feasible and economically viable with NPV, benefit cost ratio and IRR of Rs. 1126722.09, 3.92 and 29.36 per cent, respectively. The major problems faced by the machine owners was the high cost of machines and their maintenance, non-availability of trained machine operators and coverage of long distances in different states/ districts. Cooperative model of custom hiring as successfully operated in Punjab should be introduced in different states to facilitate easy availability of machines to the farmers with uniform rates to overcome the problem of scarcity of labour during peak farm operation period, reduce cost of machines and harvesting and threshing charges.